2002
DOI: 10.1590/s0021-75572002000100009
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da desnutrição precoce e reabilitação nutricional em ratos

Abstract: Objective: to verify the effects of malnutrition and nutritional rehabilitation regarding seizure threshold, body weight and brain weight in rats.Methods: pregnant Wistar rats and their pups were used. Part of the rat pups were submitted to a malnutrition protocol and the rest served as nourished controls. At P15, malnourished and control rats were submitted to status epilepticus induced by flurothyl; and the rehabilitation period started after recovery from seizures. At P30, all rats were submitted to single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
9
Order By: Relevance
“…Studies in rats, dogs and monkeys showed that protein restriction during pregnancy affects body weight and the number of muscle fibers of offspring (Nascimento et al, 1990;Oliveira et al, 1999;Nunes et al, 2002). In this study, animals began the period of malnutrition at 21 days of life, and after 45 days, they showed reduced food intake and body weight compared with the nourished group.…”
Section: Discussionmentioning
confidence: 60%
“…Studies in rats, dogs and monkeys showed that protein restriction during pregnancy affects body weight and the number of muscle fibers of offspring (Nascimento et al, 1990;Oliveira et al, 1999;Nunes et al, 2002). In this study, animals began the period of malnutrition at 21 days of life, and after 45 days, they showed reduced food intake and body weight compared with the nourished group.…”
Section: Discussionmentioning
confidence: 60%
“…As alterações nutricionais, principalmente relacionadas à síntese protéica ou à mineralização, podem culminar em alterações estruturais dos tecidos dentários, bem como da forma, da posição e do tempo de erupção 3 . Quando as proteínas deixam de desempenhar seus papéis estruturais e enzimáticos passando a assumir a provisão de glicose e energia para o organismo, instala-se um estado de desequilíbrio metabólico, e quanto mais tempo durar esse desequilíbrio maiores os danos para o indivíduo que poderá apresentar quadros de anemias, hipovitaminoses e desnutrição energético-protéica, sendo este último um dos problemas de saúde publica brasileiros, especialmente em áreas mais pobres 4,5 .…”
Section: Termos De Indexaçãounclassified
“…Em contraposição, outros estudos apontam uma menor susceptibilidade a convulsões [42][43][44] . Em outros, ainda, a desnutrição não modifica a resposta comparativamente aos animais controle 45,46 . Estudos recentes, utilizando modelo de desnutrição protéica pré e pós-natal, mostram maior sensibilidade à picrotoxina, antagonista de receptores GABA A e menor sensibilidade ao ácido quinolínico, hiperestimulador do sistema glutamatérgico em ratos desnutridos em desenvolvimento 47 .…”
Section: Desnutrição E Doenças Neuropsiquiátricasunclassified